Selective neck dissection in surgically treated head and neck squamous cell carcinoma patients with a clinically positive neck: Systematic review. Issue 4 (April 2018) - Rodrigo, Juan P.; Grilli, Gianluigi; Shah, Jatin P.; Medina, Jesus E.; Robbins, K. Thomas; Takes, Robert P.; Hamoir, Marc; Kowalski, Luiz P.; Suárez, Carlos; López, Fernando; Quer, Miquel; Boedeker, Carsten C.; et al.
Abstract: Adequate treatment of lymph node metastases is essential for patients with head and neck squamous cell carcinoma (HNSCC). However, there is still no consensus on the optimal surgical treatment of the neck for patients with a clinically positive (cN+) neck. In this review, we analyzed current literature about the feasibility of selective neck dissection (SND) in surgically treated HNSCC patients with cN + neck using the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. From the reviewed literature, it seems that SND is a valid option in patients with cN1 and selected cN2 neck disease (non-fixed nodes, absence of palpable metastases at level IV or V, or large volume ->3 cm-multiple lymph nodes at multiple levels). Adjuvant (chemo) radiotherapy is fundamental to achieve good control rates in pN2 cases. The use of SND instead a comprehensive neck dissection (CND) could result in reduced morbidity and better functional results. We conclude that SND could replace a CND without compromising oncologic efficacy in cN1 and cN2 cases with the above-mentioned characteristics.